(untitled) (International journal of artificial intelligence, 2024)
By applying these measures, healthcare professionals can significantly reduce the risk of drug resistance in TB patients on an outpatient basis. The key to preventing drug resistance is to follow a treatment regimen, monitor progress, and make adjustments if necessary to treat complications or drug resistance. These actions should be part of a coordinated, patient-centered approach to TB treatment.